Sistem Informasi Geografis Penyebaran Kutu Kebul pada Tanaman Cabai Berbasis Android di Provinsi Gorontalo - Husain, Hariati; Adriani, Evie (JURNAL TEKNIK INFORMATIKA, 2020)
Production of fresh cayenne pepper with stalks in 2014 in Prov. Gorontalo amounted to 117,719 Quintal. Compared to 2013, there was a decrease in the production of 10,105 Quintal (-7.91 percent). This decrease was due to a decrease in productivity of 3.54 Quintal per hectare (-6.36 percent) and also a decrease in the harvest area of 38 hectares (-1.66 percent) compared to 2013. In addition to the area of low harvest, there are some obstacles, especially pest attacks and diseases that are always the main problem in the event of crop failure. Pests that attack cayenne pepper plants are whitefly (Bemisia tabacci). Thus, that needs to be done in tackling the pests of whitefly. The study began with a major survey covering data collection and information, field studies, and observations on the attack of whitefly pests on cayenne pepper plants, sampling of whitefly pests, and observed morphine. All quantitative data is inputted into geographic information systems (GIS) as attribute data in the GIS. Information search and access user information and communication technology through high mobility media such as smartphones. Today's thriving smartphones are smartphones with android operating systems. Android smartphones besides having high mobility, also have very useful features such as google maps and GPS. Google maps and GPS features can collaborate in an android app program creation. Application program creation is designed using android and PHP programming languages collaborated with MySQL databases as data container media. The research aims to create a geographic information system that can help chili farmers and agricultural practitioners to be able to detect early the location of the spread of whitefly (B. tabaci) before there is a decrease in the production and growth of chili pepper crops. The study also aims to analyze and determine the zoning of the spread of whitefly pests on cayenne pepper plants using geographic information systems.